Patient, provider, and clinic characteristics associated with public STD clinic patient satisfaction. Issue 2 (30th March 2005) - Mehta, S D; Zenilman, J M; Erbelding, E J
Abstract : Objectives: There is a lack of information describing levels of patient satisfaction among patients seeking sexually transmitted diseases (STD) care in a public clinic setting. We sought to identify patient, provider, and clinic characteristics associated with patient satisfaction within public STD clinics. Methods: A cross sectional survey with random sampling was conducted among patients attending two public STD clinics. Satisfaction was assessed using questions from validated national surveys. Outcomes for multivariate logistic regression analysis were ratings of overall health care and clinician. Results: 499/605 (82%) patients were enrolled. Patients were mean age 29 years, 51% male, 94% black. Lower rating of clinician technical skills (OR = 15.6 clinic A, OR  =  7.9 clinic B) and clinic environment (OR  =  3.9 clinic A, OR  =  9.6 clinic B) were associated with lower healthcare rating, as was lower rating of television/video in waiting room (OR  =  10.2, clinic A) and dysuria (OR  =  4.2, clinic B). Higher clinician rating (OR  =  0.58, clinic A) and receiving written materials (OR  =  0.44, clinic B) were protective of lower healthcare rating. Risks for lower clinician rating at clinic A were greater pain, problems getting care, lower rating of clinician technical skill, and overall health care, while receiving written materials was protective. At clinic B, lower rating of clinician technical skill and clinic environment were risks for lower clinician rating. Conclusions: Patient satisfaction was associated with modifiable provider and clinic characteristics. Results from our study indicate a need to examine whether health outcomes of STD management vary by patient satisfaction.